PENGARUH METODE MONTENSSORI TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS V SD NEGERI 55 PRABUMULIH - Mutiara Friskilia; Bukman Lian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to improve children's conceptual understanding of science learning on the human digestive system material using the Montessori method and assisted by props during the implementation of learning. This study was conducted at SD Negeri 55 Prabumulih in class V. The research method used was quantitative with the type of experimental research, quasi-experimental design form of non-equivalent control group design, pre-test and post-test. This study used a total sampling technique, meaning that the sampling technique is the same as the population, which is 50 students from classes V.A and V.B. Data analysis techniques in this study, namely normality test, homogeneity test, and hypothesis test. From the results of the hypothesis test calculation using the dependent sample t-test, the Sig. (2-tailed) value was obtained 0.000 <0.05 and the calculated t value> t table, which means that based on the hypothesis test H_0 is rejected and H_a is accepted. This means that there is an influence of the Montessori method on students' conceptual understanding.